ldentification and life cycle of Frankliniella occidentalis (Pergande) (Thysanoptera: Thripidae) in chrysanthemum (Chrysanthemum morifolium Ramat) in Piendamo, Cauca, Colombia - PALACIOS-JARAMILLO, FERNANDO; DIAZ-CASTILLO, LUIS CARLOS; ZULUAGA C., JOSÉ IVÁN; ESCOBAR-G., JORGE (Revista Colombiana de Entomología, 1994)
The thrips species found in the culture of chrysanthemum were identified as Frankliniella occidentalis (Pergande) (Thysanoptera: Thripidae). Its life cycle under laboratory conditions (T=20.75°C; R.H.=84.28%) had a duration of egg 5 days, the nymph of first instar 2-3 days, the nymph of the second instar 5-11 days, prepupa 1-4 days and pupa 2-7 days. The adults had a lifetime duration of 0-86 days (females 2-86 days, males 0-35 days). This species shows sexual reproduction with 3.62 eggs/female/day with an average pre and post-oviposition period of 2.0 and 1.94 days respectively; from reproductive couples one generation was gotten showing a sex ratio of 499: 1(11(79.82% females and 20.18% males). F. occidentalis also shows parthenogenetics reproduction of the arrhenotoky type with an average of 3.77 eggs/female/day and a pre and post-oviposition periods of 2 and 2.43 days, respectively. Twenty-eight host plant was determined in and around of crops, standing out by their predominance: Pennisetum clandestinum Hochst, Bidens pilosa L. and Emilia sanchifolia (L.) DC.